Stock Announcement Effects of UK Cross-border and National M&As for 1998-2012 - Li, Qintong (2015)
The recent trend of takeover bids is large deal and globalization. Cross-border transactions have increased rapidly these years. The expanded and diversified market offers more investment opportunities as well as more uncertain risks.